2014
DOI: 10.1097/aog.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Placental Transfusion Strategies in Very Preterm Neonates

Abstract: Results of this meta-analysis suggest that enhanced placental transfusion (delayed umbilical cord clamping or umbilical cord milking) at birth provides better neonatal outcomes than does early cord clamping, most notably reductions in overall mortality, lower risk of intraventricular hemorrhage, and decreased blood transfusion incidence. The optimal umbilical cord clamping practice among neonates requiring immediate resuscitation remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
68
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(80 citation statements)
references
References 45 publications
10
68
0
2
Order By: Relevance
“…For term and preterm neonates, delayed cord clamping is recommended. The preterm neonates born before 32 weeks of gestation with delayed cord clamping had better neuro-developmental outcomes at the age of 18 months [8,9]. Too early umbilical vein clamping, even before the first breath of the neonate, may lead to a prolonged period of low cardiac output, which along with the undeveloped self-regulation system leads to a reduction of brain blood flow.…”
Section: Transition From Foetal To Extra-uterine Lifementioning
confidence: 99%
“…For term and preterm neonates, delayed cord clamping is recommended. The preterm neonates born before 32 weeks of gestation with delayed cord clamping had better neuro-developmental outcomes at the age of 18 months [8,9]. Too early umbilical vein clamping, even before the first breath of the neonate, may lead to a prolonged period of low cardiac output, which along with the undeveloped self-regulation system leads to a reduction of brain blood flow.…”
Section: Transition From Foetal To Extra-uterine Lifementioning
confidence: 99%
“…Many studies have shown that delayed cord clamping leads to remarkable decreases in risks of morbidity such as intraventricular haemorrhage and necrotising enterocolitis in preterm infants. Delayed cord clamping provides an additional 20 to 30 ml of blood from the placenta to the infant and this additional blood volume is linked with neonatal benefits including better systemic pressure, a reduced need for inotropic support and fewer blood transfusions [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…When the umbilical cord is clamped early, relative hypoperfusion may develop and hamper the autoregulation of cerebral blood flow [1]. Previous meta-analyses have shown that the risk of intraventricular haemorrhage (IVH) at any stage is decreased with delayed cord clamping, but no differences have been observed between groups in terms of severe IVH [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In preterm neonates, DCC for at least 30 seconds has been associated with improved hematocrit levels, mean systemic blood pressure, urine output, and cardiac function after birth (10). DCC is also associated with a decrease in intraventricular hemorrhage (all grades), need for vasopressors, number of blood transfusions during the neonatal period in premature neonates, necrotizing enterocolitis, and overall mortality (10,11). In term neonates, DCC is associated with decreased iron deficiency up to 6 months of age (9,12) and improved fine-motor and social domain scores at 4 years of age, especially in boys compared to ICC (13).…”
mentioning
confidence: 99%
“…Research continues to accumulate supporting the feasibility, safety, efficacy, and benefits of DCC (7)(8)(9)(10)(11)13,17) and umbilical cord milking (12,25). Regarding cases of RBC alloimmunization, future studies need to determine the optimal duration of DCC and also whether umbilical cord milking is a safe and efficacious therapeutic option.…”
mentioning
confidence: 99%